WHIM-3D-QSPR APPROACH FOR PREDICTING AQUEOUS SOLUBILITY OF CHLORINATED HYDROCARBONS - Oman Zuas (Indonesian Journal of Chemistry, 2008)
The weighted holistic invariant molecular-three dimensional-quantitative structure property relationship (WHIM-3D-QSPR) approach has been applied to the study of the aqueous solubility (- log Sw) of chlorinated hydrocarbon compounds (CHC's). The obtained QSPR model is predictive and only requires four WHIM-3D descriptors in the calculation. The correlation equation of the model that is based on a training set of 50 CHC's compound has statistical parameters: standard coefficient correlation (R2) = 0.948; cross-validated correlation coefficients (Q2) = 0.935; Standard Error of Validation (SEV) = 0.35; and average absolute error (AAE) = 0.31. The application of the best model to a testing set of 50 CHC's demonstrates a reliable result with good predictability. Besides, it was possible to construct new model by applying WHIM-3D-QSPR approach without require any experimental physicochemical properties in the calculation of aqueous solubility.